Complementary medicine use in cancer patients receiving intravenous antineoplastic treatment - Regina Juanbeltz Zurbano; Mª Dolores Pérez-Fernández; Bianka Tirapu Nicolás; Ruth Vera García; Susana De la Cruz Sánchez; María Teresa Sarobe Carricas (Farmacia Hospitalaria)
Abstract: Objective: Complementary and alternative medicine (CAM) use has grown considerably, although there is little research on the topic in Spain. The aim of this study was to determine the prevalence of complementary medicine use in adult cancer patients at the same time as they were receiving conventional treatment in a Spanish referral cancer centre. Method: An observational, descriptive, cross-sectional study was conducted in the Ambulatory Treatment Unit during 2 consecutive weeks in March 2015. Adult patients who were receiving intravenous chemotherapy were included. Study variables were obtained from a questionnaire and medical records. Results: 316 patients were included. 32.3% of the patients reported complementary medicine use during this period and 89% were ingesting products by mouth, herbs and natural products being the most commonly used. 81% of patients started to use complementary medicine after diagnosis, and family/friends were the main source of information. 65% of the patients reported improvements, especially in their physical and psychological well-being. Significant predictors of CAM use were female gender (P=0.028), younger age (P<0.001), and secondary education (P=0.009). Conclusions: A large proportion of cancer patients receiving intravenous chemotherapy also use complementary medicine, which they mainly take by mouth. Due to the risk of chemotherapy-CAM interactions, it is important for health-professionals to keep abreast of research on this issue, in order to provide advice on its potential benefit and risks